OPTIMIZING BIG DATA INFRASTRUCTURE: A CASE STUDY ON MIGRATING CLOUDERA HADOOP PLATFORM TO AWS - Raghavendra Sirigade (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article examines the successful migration of a Big Data infrastructure from Cloudera Data Platform (HDP) to Amazon Web Services (AWS). The study details the main goals of the project, including cost reduction, performance enhancement, and improved scalability. Through a comprehensive analysis of the migration strategy, the article highlights the critical steps taken to ensure a smooth transition, addressing key challenges such as data transfer, system compatibility, and minimizing downtime. The results demonstrate significant benefits, including a 30% reduction in infrastructure costs, 40% improvement in job processing times, and enhanced scalability. By sharing insights and lessons learned, this article aims to guide Big Data infrastructure through cloud migration, showcasing the potential for improved efficiency and performance in data-intensive environments.